Lecturer Performance Evaluation System Using Simple Multi Attribute Rating Technique (SMART) Method in STT Wastukancana Purwakarta - Gito Resmi, Mochzen; Defriani, Meriska; Sri Andar Muni, Lise; Kaniawulan, Ismi; Hasanah, Nurul (RISTEC : Research in Information Systems and Technology, 2023)
The use of a decision support system (DSS) can help someone in making accurate and targeted decisions. Many problems can be solved by using this decision support system, one of which is to assess the performance of lecturers. In determining the assessment of lecturer performance, there are several criteria that must be possessed by each individual to be used as an assessment of lecturer perfomace. The method that can be used for this decision support system is the Simple Multi-Attribute Ratting Technique (SMART) method. This study aims to provide an ssessment of the performance of lecturers at STT Wastukancana to improve the quality of internal and external services.